Co-delivery of dual chemo-drugs with precisely controlled, high drug loading polymeric micelles for synergistic anti-cancer therapy. (16th December 2019) - Wu, Yuchen; Lv, Shixian; Li, Yongjuan; He, Hua; Ji, Yong; Zheng, Mingfeng; Liu, Yong; Yin, Lichen
Abstract : The introduction of donor-receptor coordination between micelles and drug payloads provides a precise co-delivery strategy for two different chemo-drugs with high drug loading and ROS responsiveness. Abstract : Simultaneous delivery of multiple chemotherapeutics using polymeric micelles often suffers from unsatisfactory drug loading, drug ratio management, and drug release. Herein, we report a feasible strategy to prepare micelles with ultra-high drug loading and a controllable drug ratio through the introduction of donor–acceptor interactions between drugs and polymeric carriers. An amphiphilic copolymer modified with phenylboronic acid moieties on the hydrophobic segment was synthesized, in which phenylboronic acid functioned as an electron acceptor and formed donor–acceptor coordination with doxorubicin (DOX) and irinotecan (IR). The obtained dual-drug-loaded micelles possessed high drug loading (up to 50%), a tunable drug ratio, and a uniform particle size. Furthermore, both of the encapsulated drug cargoes could be effectively and selectively released in cancer cells with over-produced reactive oxygen species (ROS), and thus the drug-loaded micelles exhibited synergistic anticancer efficacy and reduced systemic toxicity.